2021
DOI: 10.3389/fpsyg.2021.669384
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Examination of the Coronavirus Anxiety Scale and the Fear of Coronavirus Disease 2019 Scale in the Italian Population

Abstract: The coronavirus disease 2019 (COVID-19) outbreak has caused not only significant physical health problems but also mental health disorders. Anxiety and fear appear to be the main psychological symptoms associated with COVID-19. The aim of this study was to investigate whether anxiety and fear related to COVID-19 are influenced by sociodemographics and whether specific conditions, such as positivity for COVID-19 or death among relatives and friends, can further enhance these symptoms. In this cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 29 publications
3
22
0
2
Order By: Relevance
“…Many studies reported higher fear of COVID-19 and threat perception in females ( Nguyen et al, 2020 ; Reznik et al, 2020; Sakib et al, 2020 ). Similar results were obtained in studies for COVID-19 anxiety ( Akyildiz and Durna, 2021 ; Bhattacharya et al, 2021 ; Orrù et al, 2021 ). On the other hand, some studies showed that males have higher COVID-19 anxiety levels ( Ashoor et al, 2021 ; Curtis et al, 2021 ; Saravanan et al, 2020 ; Srivastava et al, 2020 ).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Many studies reported higher fear of COVID-19 and threat perception in females ( Nguyen et al, 2020 ; Reznik et al, 2020; Sakib et al, 2020 ). Similar results were obtained in studies for COVID-19 anxiety ( Akyildiz and Durna, 2021 ; Bhattacharya et al, 2021 ; Orrù et al, 2021 ). On the other hand, some studies showed that males have higher COVID-19 anxiety levels ( Ashoor et al, 2021 ; Curtis et al, 2021 ; Saravanan et al, 2020 ; Srivastava et al, 2020 ).…”
Section: Introductionsupporting
confidence: 88%
“…In most studies conducted in North America, females had higher levels of COVID-19 related fear and anxiety than males (Camacho et al, 2020; Grande and Doyle-Baker, 2021 ; García-Reyna et al, 2021 ; Gélinas et al, 2021 ; Landa-Blanco et al, 2021 ; Lee et al, 2020 ; Pérez-Fuentes et al, 2020 ; Ojalehto et al, 2021 ). In addition, studies conducted in Europe, female's COVID-19 related fear and anxiety levels were higher ( Bakioğlu et al, 2020 ; Kaçoğlu et al, 2021 ; Morales-Rodríguez, 2021 ; Orrù et al, 2021 ; Tsipropoulou et al, 2020 ; Ypsilanti et al, 2021 ). On the other hand, some studies conducted in Middle East countries showed that males had higher levels of COVID-19 related fear and anxiety than females ( Abdelgwad and Abdelaziz, 2021 ; Alnazly et al, 2021 ; Ashoor et al, 2021 ; Ghaderi et al, 2021 ; Saravanan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since COVID-19 and the highest mortality and complication rate were found in elderly subjects during the outbreak, it is not surprising that older CV patients are more likely to be psychologically affected, as reported in several general populations [23][24][25][26][27]. However, some studies reported lower levels of COVID-19 fear in older subjects than in young to middle-aged adults [21].…”
Section: Discussionmentioning
confidence: 88%
“…The coronavirus pandemic, which quickly crossed the borders of all countries, brought dramatic changes to people’s lives in various ways and affected all age groups. Although physical symptoms of the disease were a priority in the treatment of patients with coronavirus disease, the disease also caused significant mental problems [ 1 ], of which a significant increase in fear [ 2 ] associated with greater depression, stress and anxiety dominated [ 3 , 4 , 5 ]; these experiences were especially on the rise in the first months of the pandemic [ 6 ]. The possibility of accentuating already existing psychological influences due to new waves of coronavirus disease generates significant challenges and requirements for mental health professionals.…”
Section: Introductionmentioning
confidence: 99%